Antioxidant and Antibacterial Activities of Different Extracts and Fractions of a Mangrove Plant Sonneratia alba - Mohammad Moneruzzaman, Khandaker; Imdadul, Haq; A.B.M., Sharif Hossain (2014)
A study was carried out to investigate the antioxidant potential and antibacterial activities of ethanol, methanol and chloroform extracts from soil grown and tissue culture explants of the mangrove plant Sonneratia alba, as well as its ethyl acetate and water extracted fractions. Antioxidant effects were determined by DPPH and SOD assays while antibacterial activities were determined using the agar disk diffusion method. LC-MS/MS analysis was also conducted in an attempt to identify active compounds in the extracts and fractions. The results showed that both the methanol and ethanol extracts of leaf and bark exhibited potentially good antioxidant and antibacterial activities compared to the chloroform extracts. There was a positive correlation between the total phenolic content and the antioxidant effects of the ethanol and methanol extracts of leaf and bark (R2 = 0.72). Among the crude extracts, the ethanol extract of bark exhibited the best antioxidant and antibacterial activities. Chloroform extracts of both leaf and bark samples exhibited lower antioxidant and antibacterial activities. On the other hand, water extracted fraction showed better antioxidant activity compared to ethyl acetate extracted fraction. All the extracts showed good antioxidant activity with IC50 values ranging between 0.019-0.37 mg mL-1. LC-MS/MS analysis revealed 8 peaks at m/z values of 331, 345, 452, 463, 473, 480 and 494 with fragmentation patterns corresponding to the high antioxidant activity of the water extracted fraction. This study has shown that there are metabolites in S. alba that have the potential to serve as antioxidant and antibacterial compounds that may serve as a lead to the development of new pharmaceuticals.